Pentingnya manajemen investasi dalam menjaga minat investor terhadap saham perbankan syariah - Latifah, Zahro Nur (Maliki Interdisciplinary Journal, 2024)
Islamic Banking is a type of banking that operates based on Sharia principles. It has gained popularity in Indonesia. The functions of Islamic Banking are similar to those of Conventional Banking, which include managing public funds, collecting and distributing funds. The bank is able to distribute funds by using the funds it owns or through funds collected from investors. One way in which the bank can acquire funds is through investors who purchase bank shares via the capital market. Investors invest in these shares to earn profits or to receive returns from the bank. The bank then uses these incoming funds from investors to provide financing, and the profit earned from this financing will be shared between the bank and investors. That is why it is crucial for Islamic Banking to properly manage investment funds to maintain the interest of stock investors in Islamic Banking shares.